Return of the Maltese Falcon - Collins, Max Allan (Hard Case Crime book., 2026)
Hardboiled noir that picks up where legendary author Dashiell Hammett left off, telling the story of iconic private eye Sam Spade and the quest for the priceless Maltese Falcon. Legendary mystery writer Dashiell Hammett only wrote one novel about detective Sam Spade: The Maltese Falcon, the most famous private eye story ever told. But the case was never really solved - the priceless golden, bejeweled bird that men and women had been dying to possess turned out to be a fake. Now, Mystery Writers of America Grand Master Max Allan Collins (author of Road to Perdition) brings closure to this crime classic, reuniting all the surviving members of the original cast alongside femme fatales, crooked collectors, and greedy gangsters for one more thrilling, deadly chase through the streets, wharves, morgues, bars, and back alleys of 1920s San Francisco - and finally answers the question, Whatever became of the Maltese falcon...?